Public Service Performance in the Land Office of Pangkalpinang City - Rony Kurniawan (Green Publisher Indonesia, 2021)
This research’s background was the assumptions that services in the land sector are still too difficult and convoluted. This study’s problems are how the performance of the Land Office of Pangkalpinang in providing service and the supporting and restraining factors. This research is a descriptive study with a qualitative approach. Collecting data through in-depth interviews, observation and documentation. The data were gathered from 15 employees who were the sample in this study. The results bring a conclusion that the performance of the Land Office of Pangkalpinang has generally been running well and fulfilling the public’s expectations. The indicators are (a) Effectiveness, (b) Responsiveness, in recognizing and knowing the public’s needs, and (c) Accountability, on doing their duties and functions that followed the organizational vision and mission. Internal and external factors that influence the performance are (a) The ability of employees, an internal factor, (b) Motivation, (c) Public participation, an external factor that is inadequate in supporting office performance; (d) Communication factors.